HUBUNGAN TINGKAT PENGETAHUAN IBU, POLA ASUH, ASUPAN GIZI TERHADAP STATUS GIZI (BB/TB) PADA BALITA 24-59 BULAN DI WILAYAH KERJA PUSKESMAS ANAK AIR KOTA PADANG - Nova, Maria; Misdhal Rini, Alya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Wasting is a condition where there is a problem of malnutrition where a toddler's weight does not match the proper body weight with a z-score value of >- 2SD. Wasting is a symptom of acute under nutrition, usually occurring due to inadequate food intake, inadequate parenting patterns, maternal knowledge, education and income level. This study aims to determine the relationship between maternal knowledge, parenting patterns, and nutritional intake on nutritional status (BB/TB) in toddlers 24-59 months. The type of research used is descriptive-analytic with a Case-Control research design. The sampling technique was purposive sampling of 44 respondents. Data on maternal knowledge and parenting patterns used a questionnaire, while nutritional intake used the Semi Quantitative Food Frequency Questionnaire (SQFFQ). Data analysis used the Chi-square test. The research results showed that 68.2% of mothers' knowledge was good in the control group, 18.2% of mothers' knowledge was good in the case group, 86.4% good parenting patterns in the control group, 45.5% poor parenting patterns in the case group, 59 .1% good carbohydrate intake in the control group, 18.2% poor carbohydrate intake in the case group, 86.4% good protein intake in the control group, 40.9% poor protein intake in the case group, 86.4% good fat in the control group and 45.5% less good fat intake in the case group. From the results of statistical tests, there is a significant relationship between maternal knowledge, parenting patterns, carbohydrate, protein and fat intake and the incidence of wasting. Maternal knowledge, parenting patterns, intake of carbohydrates, protein and fat are risk factors for wasting in toddlers. It is hoped that the public will know the importance of nutritional knowledge, parenting patterns, nutritional intake and other risk factors in toddlers so that they can prevent wasting.Keywords: wasting, maternal knowledge, parenting, carbohydrate intake, protein intake, fat intake